Bradyarrhythmia as a presenting feature of subclinical hyperthyroidism - Neki, NS (Journal of Medicine, 2016)
Subclinical hyperthyroidism appears to be a common disorder. It may be caused by exogenous or endogenous factors: excessive TSH suppressive therapy with L-thyroxine (L-T4) for benign thyroidnodular disease, differentiated thyroid cancer, or hormone over-replacement in patients withhypothyroidism are the most frequent causes. Consistent evidence indicates that subclinicalhyperthyroidism reduces the quality of life, affecting both the psycho and somatic components ofwell-being, and produces relevant signs and symptoms of excessive thyroid hormone action, oftenmimicking adrenergic overactivity J MEDICINE January 2016; 17 (1) : 39-40